Penerapan Linq(Language Integrated Query) Untuk Implementasi Aplikasi Perpustakaan - Sri Siswanti, Yoshua Hendra P, Yustina Retno W U (Jurnal Ilmiah SINUS, 2014)
LINQ is new technology to create even window or web application. This research focus on how to implemented LINQ at Library application. The application is compiled by following a three-layer architecture rule, which is known as 'three tier'. A 'Three tier' architecture is divided into three parts, they are data tier, business tier, and presentation tier. Data tier is data in the form of a database, business tier is data in the form of services which consists of different functions that consumes the data tier, and the last one is presentation tier which takes the form of applications interface that consumes business tier.The stored information will be consumed through a special class called business logic class that will handle various operations, such as insert, update, and delete the data book. LINQ is needed to create this business logic class that allows data access and aims to facilitate query to all types of data such as Object, XML, databases, etc. This LINQ enables a programming language which is used on the Microsoft NET framework has a native query capabilities towards the data. The LINQ statement is written using C#.net with Visual Studio 2010 and DevExprees 2012 with SQLServer database. The system design uses UML. The result is library application using LINQ framework. Kata Kunci : Library application, LINQ, LINQ to SQL, Web service, WCF, SOA, Prototype.